Comparison of Angiographic and in Hospital Outcomes of Thrombuster Versus Pre Ballooning in Primary Percutaneous Coronary Intervention - Muhammad Abbas Khan, Sajjad Ali, Muhammad Yousaf, Inam-U-Llah, Mahmood Ul Hassan (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: South Asian communities vary from western cultures in terms of their genetic make-up, culture, and predisposition to develop coronary artery disease (CAD). Percutaneous coronary intervention (PCI) has shown remarkable effectiveness over the last three decades. To decrease hospital outcomes, thrombus aspiration and pre ballooning are often employed during angiography. Objectives: To evaluate the angiographic and hospital results between PCI using a thrombuster and PCI using pre-ballooning. Methodology: This research was conducted at Hayatabad Medical Complex, Peshawar from March 2022 to September 2022. 188 patients who came in for primary PCI at the catheterization lab were included and divided into two groups: the “thrombuster group (n=96)”and the “balloon group (n=92)”. In the thrombuster group, manual thrombus aspiration was carried out with the use of a thrombuster, whereas in the balloon group, patients had primary PCI with customary pre-dilatation using a balloon and had their TIMI flow evaluated and graded again. Throughout their hospital stays, all patients were monitored, and study outcomes, such as death and post-procedure problems, were noted. The statistical study made use of SPSS (v.25), and p value less than 0.05 was established as the threshold for significant. Results: 54 participants (26.72%) were women and 134 (71.72%) were men. A statistical study reveals a significant relationship (p=0.027) between gender. With a larger percentage of male patients (36.70%), the balloon group’s demographics (n=92; 48.93%) differed from those of the thrombuster group (n=96; 51.06%). In balloon groups, a greater mean age (56.89 10.3) was discovered. With the exception of smoking, all clinical risk factors were greater in balloon groups than in thrombuster patients [17 (9.04%) vs. 12 (6.38%); p=0.007]. When compared to the balloon group (7/92), the Thrombuster groups’ in-hospital mortality rate was much lower (2/96). Overall complications were also substantially greater with balloon than with thrombuster. Conclusion: Thrombus aspiration rather than ballooning should be performed using a large lumen guiding catheter in a deep-seated position. Keywords: angiography, coronary artery disease, thromboses, ballooning, angiography